CONCEPT DIGITALIZATION APPARATUS: INTERACTION OF REAL AND VIRTUAL SECTORS OF ECONOMY BASED ON THE SUPPLY CHAIN STRATEGY - Ukolov, Vladimir F.; Cherkasov, Vitaly V. (International Journal of Supply Chain Management, 2019)
Abstract- The present paper studies the insufficiently studied problem of creating a conceptual apparatus for the practice of interaction between enterprises of the real and virtual sectors of the economy. The author sets a goal to analyze various aspects of this problem and formulate a number of concepts expanding and clarifying the system of ideas about the interaction of the real and virtual sectors of the economy. The aim of the study is to develop and practice the basic concepts and clarify the foundations of interaction between the real and virtual sectors of the economy, which will expand, introduce and more fundamentally understand the essence of this phenomenon and reduce the risks of making many management decisions. The study used the methods of situational, structural and dynamic analysis contributed to the study of the current ideas about the interaction of enterprises of the real and virtual sectors of the economy, including government regulation of emerging problems. A systematic approach was used when assessing the state of adaptation of digital enterprises. Research has revealed the systemic nature of the influence of a combination of various factors affecting the interaction of economies, all aspects of the life of enterprises in the real sector of economy, their internal and external functioning environment that need to be considered when describing interaction phenomena and the concepts arisen from their essence. The practical significance of the study materials: The materials of the paper are of practical value for business structures, public administration and the public sector. The formulated concepts are used in practice in the transition of enterprises in the real sector of the economy to digitalization and management of processes of interaction between the real and virtual sectors of the economy. Their use contributes to the formation of the most complete picture of the management object as well as the adoption of adequate management decisions about its change in a given direction, increasing their competitiveness and profitability.